Pulmonary Cavitation Following Acute Section Pulmonary Infarction: A Rare Case of Complication of Pulmonary Embolism - Sushant Dilip Muley; Sushant Hiraman Meshram; Ashish Kendre; Pranav Atigre (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Pulmonary infarction is a rare complication of Pulmonary Embolism (PE) due to dual blood supply of the lung. Pulmonary cavity formation following PE is a very rare but a recognised complication, typically resulting from ischaemic infarction of lung parenchyma. The majority of reported cases involve patients managed conservatively with anticoagulation or thrombolytic therapy, without surgical or invasive intervention. Cavity formation occurs due to occlusion of distal pulmonary arteries, leading to haemorrhage, necrosis and subsequent parenchymal breakdown. The authors report a rare case of a 35-year-old male patient with no known co-morbidities presented with acute PE with pulmonary infarction leading to cavitation with possible secondary infection following a thrombolysis and anticoagulation therapy. Chest radiography showed prominent descending right pulmonary artery-(Palla sign). As patient was haemodynamically unstable, he was immediately thrombolysed with intravenous Streptokinase (STK) followed by systemic anticoagulation with unfractionated heparin. Patient discharged on tab dabigatran 150 mg twice daily in a stable condition. This case highlights the importance of vigilance for post-embolism complications such as cavitation and infection, even after appropriate anticoagulant management and need for prompt management to prevent associated morbidity and mortality thereby improving the quality of life of the patient.